Enhancing student comprehension of crystal structures: The effectiveness of Vesta as a learning tool - Khoirotun Nadiyyah; Rika Aprianti; Zakirman Zakirman; Widiasih Widiasih; Fadhila Ulfa Jhora; Ratnawulan Ratnawulan (Universitas PGRI Kanjuruhan Malang, 2025)
The advancement of technology in education was evident in the development of digital-based learning media. It was expected to serve as a stimulus in transforming knowledge for students, particularly in abstract subjects such as crystal structures. Understanding crystal structures was crucial for studying the physical properties of materials, making it important for students to enhance their comprehension. The research objective was to determine the effectiveness of using Vesta software as a learning media to enhance students' understanding of crystal structures by employing standardized assessment instruments. This research was conducted using a quantitative approach focused on collecting numerical data and statistical analysis through an experimental method involving two groups of students taking a solid-state physics course. The research design involved a control and an experimental group. Both groups were given the same subject but using different learning media. The instrument used was a multiple-choice test that had been rigorously validated through validity, reliability, difficulty level, and discrimination index. Effectiveness was evaluated using independent sample t-test analysis with the aid of SPSS software. Instrument testing data revealed that out of 40 developed questions, 20 met the standards to be used as instruments. The results indicated a highly significant enhancement in students' understanding of crystal structures after using the Vesta software as a learning media, as represented by a sig. (2-tailed) value of 0.000. The findings indicate that Vesta can be integrated into science teaching. Further research can test the effectiveness of implementing Vesta in distance learning.